Designing Ergonomic Work Aids to Improve Worker Productivity in Spring Mattress Manufacturing at PT Rentang Buana Niagamakmur - Steven Lias; Daniel Kurniawan; David Lihan; Andrean Gunawan; Thedy Yogasara; Sani Susanto (Ann Publisher, 2026)
Background. PT Rentang Buana Niagamakmur is a spring mattress manufacturing company that faces a decrease in productivity due to worker discomfort and ergonomically suboptimal working postures Purpose. This study aims to identify the causes of workers' physical discomfort in the production process and design work aids that can improve comfort and productivity. Method. The research process began with data collection through observation and interviews to understand the activities of workers at the production station. The Nordic Body Map (NBM) was employed to identify workers’ musculoskeletal complaints, while Rapid Entire Body Assessment (REBA) was applied to evaluate ergonomic risk levels. Results. Based on the results of the analysis, the design of work aids was carried out using an ergonomic approach that suits the needs of workers at fabric measurement and foam cutting stations. Evaluation of the effectiveness of the aids was carried out by comparing REBA scores before and after the use of the aids. Conclusion. The results showed that the main physical complaints of workers were identified in the right wrist, waist, and calf. The design of work aids at the fabric measuring station lowered the REBA score from 11 to 3 (low risk), while the aids at the foam cutting station reduced the score from 7 to 3 (low risk). Implementation. The proposed work aids were shown to significantly reduce physical discomfort and improve productivity at both workstations.